Microstructure and Mechanical properties in Cu-17Al-11.4Mn shape memory alloys laser welded to 316L stainless steel - Simões, Bernardo João Ribeiro (2021)
It is well known that NiTi alloys are the most widely used shape memory alloys nowadays, with a large number of possible applications, such as in the aerospace, auto motive, medical and civil industries. This large versatility makes them a very difficult alloy to replace. However, there is a group of shape memory alloys which has been receiving ev ermore attention as a candidate to replace NiTi alloys, with many of the same applica tions. These are the Cu-Al-Mn alloys, a lightweight group of alloys recognized for their large versatility and lower cost, while managing to achieve the same or even better results than NiTi in certain scenarios, specially the Cu-17Al-11.4Mn (at. %) alloy. However, little is known about how this alloy’s properties behave when welded to other materials, which leaves a lack of knowledge regarding this alloy’s versatility on this issue. In this dissertation, this alloy laser welded to stainless steel to study the welding process’s effects on it together with the influence of the 316L low carbon stainless steel it is welded to. For this effect, the welded alloy was subjected to microstructural and mechanical testing, such as Scanning Electron Microscopy, Electron Backscatter Diffraction, Energy-Dispersive X-ray Spectroscopy and X-ray Diffraction, as well as Microhardness Mapping, Mechan- ical Cycling and Uniaxile Tensile Testing. This study shows that the welding process heavily influences the microstructural composition of the fusion zone, such as grain size and orientation while, on a mechanical level, also reinforcing the alloy’s superelastic properties together with the steel.